O PRINCÍPIO DA PRIMAZIA DA RESOLUÇÃO DO MÉRITO COMO FORMA DE ACESSO À JUSTIÇA (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The article brings an approach about the principle of the primacy of the resolution of merits as a form of access to Justice. The objective is to understand the effects according to the Brazilian Judicial System. Initially, it was adresses the precept of the principle of the primacy and its characteristics so that the examination of the primacy of the judgment on the merits could be highlighted, in order to present its effects in the implementation of procedural constitutional principles. The results identified that these resources are still being improved from the improvement present in the Civil Procedure Code of 2015, thus fitting their use according to the needs of each case. The article was produced from a descriptive study and bibliographical approach.